Effect of Regular Nursing Rounds Based on Ethical Care on Patient Satisfaction with Nursing Care Quality and Patient Anxiety: a Quasi-Experimental Study - Hamideh Parsapoor; Mitra Talebi; Zeinab Mousivand; Naser Kamyari; Naeime Nankali; Mona Damavandi; Fateme Najafi; Nasrin Zamani; Mahnaz Alizade; Narges Mohamadi parsa; Elham Mahmoodi (Hamadan University of Medical Sciences, 2022)
Background and Objective: Considering the importance of respecting the rights and satisfaction of patients, as well as the destructive role of anxiety in patients' recovery processes, the present study aimed to evaluate the effect of regular nursing rounds based on ethical care on the level of satisfaction and anxiety of hospitalized patients. Materials and Methods: This quasi-experimental study was conducted based on a pre-test-post-test design in Fatemieh Hospital in Hamadan, Iran. A total of 100 hospitalized patients were assigned to two groups of control and intervention (n=50 in each group), and patients in the intervention group received a clinical round based on ethical care, in addition to routine care. The control group also received routine care. Finally, the difference between the mean scores of satisfaction of nursing services and the anxiety of the two groups before and after the intervention was analyzed in SPSS V.20 software using descriptive and inferential tests. Results: The two groups of intervention and control were not statistically significant in terms of underlying variables and disease and were homogeneous. In the intervention group after receiving the relevant training, anxiety decreased and the level of patients' satisfaction with the quality of nursing care increased significantly, as compared to patients in the control group; therefore, the intervention was effective (P<0.001). Conclusion: Considering the effect of clinical rounds based on ethical care on anxiety and patients' satisfaction with the quality of nursing care, it is recommended to be used as an intervention in therapeutic wards.